Feasibility, acceptability, patient experience, and preliminary efficacy of a virtual reality guided imagery intervention for chronic pain - Doan, Lauren; Recasens, Marc; Lake, Jessica; Miller, Ian; Vierra, Elise; Richeimer, Steven; Yao, Iris; Junghaenel, Doerte U.; Weinstein, Faye (Frontiers in Digital Health, 2025)
ObjectivesGuided imagery is a strategy utilized in chronic pain management by patients. Benefits are cumulative via ongoing application. Engagement via Virtual Reality (VR) is becoming more accessible as a strategy to enhance adherence, use and benefit of guided imagery. We conducted a preliminary investigation of the feasibility, acceptability, patient experience, and efficacy of the use of VR for patients with chronic pain to use at home.Methods36 patients with Complex Regional Pain Syndrome or Low Back Pain were randomly assigned to VR or audio only guided imagery groups. Feasibility, acceptability and patient experience were rated by participants. Outcomes assessed at baseline and post-intervention were pain, mental and physical health, and mood.ResultsResults indicate that the intervention was feasible and found acceptable by participants. The intervention also demonstrated promising preliminary efficacy based on self-reported within-group decreases in pain, depressive symptoms, anxiety symptoms and improvements in physical and mental functioning.ConclusionsThe use of VR shows promise for enhancing the application and experience of guided imagery training with people who have chronic pain.